Four days; the historical record of the death of President Kennedy - United Press International; American Heritage ([New York] American Heritage Pub. Co., 1964)
The events from the moment of President Kennedy's assassination to his burial three days later.
Keywords: Kennedy, John F. -- 1917-1963 -- Assassination; Kennedy, John F. -- 1917-1963 -- Death and burial